The The Signage Placement Directions On The Pedestarian Path, Iskandar Muda Road, Medan City - Hibnul Walid; Indra Kesuma Hadi; Muhammad Amin; Surta Ria Nurliana Panjaitan; Rizky Franchitika (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
The city of Medan as the capital city of North Sumatra Province has made significant progress. This coTechnology and Computer Sciencemmercial buildings in several places, one of which was in the Jalan Iskandar Muda corridor. In general, these buildings are spread along road corridors that function as commercial areas in the city of Medan. Presence signage on Jalan Iskandar Muda, Medan City, it turns out that they tend to maximize the economic potential of the region, resulting in a shift in the function of urban space into a space for advertising media expression. As an effort to create city comfort that supports visual aesthetics and does not interfere with pedestrian comfort, this research produces a design concept in the form of placement signage according to the designated zone, namely in the pedestrian zone, the design of the height proportion signage to the width of the pedestrian path using a human scale approach, panel or plane dimension design signage by using the concept golden section, as well as setting the point of placement or spread signage using the concept of rhythm and local regulations that have been established with the aim of limiting the number of signage on the pedestrian path.